2023
DOI: 10.1088/1742-6596/2484/1/012023
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of micro and nano material with aluminum alloy (Al7075) metal matrix composite: a review

Chandra Shekhar Koria,
Rajan Kumar,
Premanand S Chauhan

Abstract: The characteristics and structural performance of a composite material’s properties are better than those of its component parts because It comprised of a pair or more insoluble, chemically separate stages. functioning alone. ‘Metal-Matrix’ composites materials that have been produced from metals and ceramics had fibers or particles incorporated into them to enhance their physical characteristics. The fabrication of several parts and components in the aircraft and aerospace industry regularly uses aluminium 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been found that the inclusion of graphene in the aluminium matrix enhances the material's strength and hardness while retaining the high ductility of the matrix. The thermal and electric conductivity of the graphene-reinforced aluminium matrix composites were also significantly improved [6][7][8][9]. As a result, such composites have significant potential for development and application in a variety of fields, including electronics, aviation, and automotive industries [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the inclusion of graphene in the aluminium matrix enhances the material's strength and hardness while retaining the high ductility of the matrix. The thermal and electric conductivity of the graphene-reinforced aluminium matrix composites were also significantly improved [6][7][8][9]. As a result, such composites have significant potential for development and application in a variety of fields, including electronics, aviation, and automotive industries [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Aluminium and its alloys are also suitable as matrices of composite materials. The use of aluminium in composites makes it possible to further improve the properties of composites, such as hardness and the modulus of elasticity, while reducing the density of the material at the same time [7,8].…”
Section: Introductionmentioning
confidence: 99%